A molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte material and preparation method thereof

By adopting molybdenum-doped lithium germanium phosphorus and sulfur solid electrolyte material, the existing all-solid lithium battery electrolyte materials have been solved, and high conductivity, low cost and good stability have been achieved, and materials are prepared with high conductivity, low cost and good stability, which are suitable for all-solid lithium secondary batteries.

CN114824458BActive Publication Date: 2025-04-01SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210505970.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-10
Publication Date
2025-04-01
Estimated Expiration
2042-05-10
Patent Text Reader

Abstract

The present invention discloses a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material and a preparation method thereof, relating to the field of solid electrolytes. Li2S, GeS2, MoO3, and P2S5 are ground and mixed under an inert atmosphere, and then ball-milled using a ball mill to obtain a mixed powder; the obtained mixed powder is sealed and calcined in an inert gas atmosphere to obtain a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte with the composition Li x Ge 1‑y Mo y P2S 12 , where 9.5 < x < 10 and 0 < y ≤ 2. The molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte of the present invention has good mechanical properties, excellent ionic conductivity, and good electrochemical stability, effectively solving the problems of low ionic conductivity of the Li 10 GeP2S 12 solid electrolyte and poor stability towards lithium metal, and can be used as an ideal solid electrolyte material in all-solid-state lithium secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte material and a preparation method thereof, and in particular to a solid electrolyte material having good mechanical properties, excellent ionic conductivity, and good electrochemical stability and can be used in an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have currently occupied the electric vehicle market in my country and are also being used on a large scale in the grid energy storage market. Battery technology is one of the key technologies to solve the current energy problem. In electric vehicles, energy density is the first indicator of power battery performance, while energy storage batteries pay more attention to cost and safety. With the growth of electric vehicle sales, the frequency of safety accidents such as electrolyte leakage, spontaneous combustion and explosion has also increased significantly, and energy storage power stations have also experienced many safety accidents. Safety issues have become a key issue hindering the further application and development of lithium-ion batteries. The main reason for the safety problem is that flammable organic electrolytes are used in lithium-ion batteries, which participate in combustion and release a large amount of heat when the battery has a short-circuit thermal runaway. All-solid-state batteries use solid electrolytes for ion conduction. Compared with traditional liquid batteries, they are non-flammable and non-volatile, and the safety of the battery has been greatly improved. Therefore, they have received widespread attention from academia and industry and are considered to be one of the most promising next-generation lithium-ion battery technologies.

[0003] Solid electrolytes are the core materials of all-solid-state batteries. Most of the current solid electrolytes have low ion conductivity, unstable electrochemical window and various interface problems. These problems make the comprehensive performance of current all-solid-state batteries unable to meet the application needs, and there are no commercial products that can be launched. Among the inorganic solid electrolytes reported so far, sulfide electrolytes have attracted much attention due to their highest ionic conductivity and good mechanical properties. However, the disadvantage of lithium-sulfur systems such as Li2S and P2S5 is that they are easily hydrolyzed and oxidized, resulting in poor chemical stability. It is difficult to guarantee long-term stability and cyclability, which restricts the application of lithium-sulfur solid electrolytes. Although Li 10 GeP2S 12 The lithium ion conductivity of (LGPS) can reach the level of commercial liquid electrolytes, but its cost is relatively high, and its application in sulfide solid electrolytes remains to be studied. Therefore, it is necessary for technicians in this field to explore a solid electrolyte material with high ion conductivity and good chemical stability. The present invention replaces Ge with Mo to reduce the cost of the electrolyte, improve the lithium ion conductivity and the stability of lithium metal. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a sulfide solid electrolyte material with high conductivity, low cost and good lithium metal stability and a preparation method thereof, and applies it in an all-solid-state secondary battery, thereby improving lithium ion conductivity, reducing electrolyte costs, and improving lithium metal stability.

[0005] To achieve the above object, the present invention provides a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material in the first aspect: its chemical formula is Li x Ge 1-y Mo y P2S 12 .

[0006] As a further preferred embodiment, a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte, the range of x is preferably 9.5 <x<10。

[0007] As a further preferred embodiment, a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte, the range of y is preferably 0 <y≤0.1。

[0008] The second aspect of the present invention is to provide a method for preparing a molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte, comprising the following steps:

[0009] Step 1, according to the general formula: Li x Ge 1-y Mo y P2S 12 , weigh Li2S, GeS2, MoO3, and P2S5 in stoichiometric ratio under an inert atmosphere;

[0010] Step 2, grinding and mixing Li2S, GeS2, MoO3 and P2S5 under an inert atmosphere, and ball milling using a ball mill under an inert atmosphere to obtain a mixed powder;

[0011] Step 3, compressing the mixed powder under an inert atmosphere, placing it in a sealed container, and packaging it after evacuation;

[0012] Step 4, heating and calcining the sample in the sealed container to perform a solid phase reaction;

[0013] Step 5: After heating and calcining, naturally cool to room temperature to obtain a composition of Li x Ge 1-y Mo y P2S 12 Molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material.

[0014] As a further preferred embodiment, the molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte material: Li x Ge 1-y Mo y P2S 12, of which 9.5 <x<10,0<y≤0.1。

[0015] As further preferred, the inert atmosphere is argon, the water content of argon is less than 1 ppm, and the oxygen content is less than 1 ppm;

[0016] As further preferred, the rotation speed of the ball mill in step 2 is 300-500 rpm, and the ball milling time is 5-30 hours.

[0017] As further preferred, in the step 3: the ball-milled mixed raw material is pressed into a sheet to prepare a sheet-like mixed raw material.

[0018] As further preferred, the thickness of the flaky mixed raw material is 1 to 15 mm.

[0019] As further preferred, in step 4, the heating and calcining temperature is 500-650° C., and the solid phase reaction time is 5-48 hours.

[0020] As a further preferred method, the Li obtained in step 5 x Ge 1-y Mo y P2S 12 The molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material is made into powder.

[0021] As a further preferred embodiment, Li x Ge 1-y Mo y P2S 12 The molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte material is made into powder with a particle size of 10-1000 microns.

[0022] The third aspect of the present invention provides an application of the molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material prepared by the above method in an all-solid-state secondary battery.

[0023] In general, the above technical solutions conceived by the present invention have the following beneficial effects compared with the prior art:

[0024] (1) The novel molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material of the present invention has good chemical stability;

[0025] (2) Li obtained from the novel molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte of the present invention x Ge 1-y Mo y P2S 12 It has good ionic conductivity, reduces the activation barrier of lithium ion migration, and effectively solves the low ionic conductivity of sulfide solid electrolytes;

[0026] (3) Lithium x Germanium 1-y Molybdenum y P2S 12 The sulfide solid electrolyte improves the interfacial stability towards lithium metal in the application of lithium symmetric batteries, exhibits good cycling performance, and effectively solves the problem of poor stability of 10 Germanium Phosphorus Sulfide 12 the sulfide solid electrolyte towards lithium metal;

[0027] (4) Lithium x Germanium 1-y Molybdenum y P2S 12 The sulfide solid electrolyte has a simple preparation process, strong reproducibility, is suitable for large-scale production, and can be used as an ideal solid electrolyte material in all-solid-state lithium secondary batteries.

[0028] (5) Lithium x Germanium 1-y Molybdenum y P2S 12 The sulfide solid electrolyte has good mechanical properties. Further mechanical operations such as rolling and powdering can improve its adaptability during the assembly process of all-solid-state batteries.

[0029] The concept, specific structure and technical effects of the present invention will be further described below to fully understand the purpose, features and effects of the present invention. Detailed Embodiments

[0030] The endpoints and any values disclosed herein are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, between the endpoints of each range, between the endpoints of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0031] The first aspect of the present invention provides a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material Li x Germanium 1-y Molybdenum y P2S 12 , where 9.5 < x < 10 and 0 < y ≤ 0.1. This solid electrolyte material has good mechanical properties, can be made into film, sheet or powder form, and the roughness and particle size can be adjusted as needed.

[0032] The second aspect of the present invention provides a method for preparing a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material, comprising the following steps: grinding and mixing solid electrolyte raw materials Li2S, GeS2, MoO3, and P2S5 according to a stoichiometric ratio, and ball milling with a ball mill, followed by film making, heating, calcining, and cooling. The surface roughness of the solid electrolyte is controlled by controlling the ball milling time and the rotation speed, and then cooperates with the positive and negative electrode materials to reduce the contact resistance, while improving the strength and toughness of the solid electrolyte. Preferably, the ball milling conditions include: the rotation speed can be specifically 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 600rpm or any value between the aforementioned values, more preferably 500rpm. The ball milling time can be specifically 3 hours, 5 hours, 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 40 hours or any value between the aforementioned values, more preferably 20 hours.

[0033] The third aspect of the present invention is to provide an application of a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte in an all-solid-state secondary battery. Specifically: molybdenum-doped lithium germanium phosphorus sulfur is used as a solid electrolyte and assembled with a positive electrode and a lithium metal negative electrode into an all-solid-state lithium secondary battery. The chemical stability of the molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte significantly improves the compatibility with positive and negative electrode materials, and can be used with a variety of electrode materials to form a battery for cycle testing. Preferably, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, nickel manganese binary, nickel cobalt manganese ternary, lithium iron phosphate, nickel cobalt aluminum oxide, and lithium-rich manganese-based positive electrode materials. Preferably, the lithium metal negative electrode includes at least one of pure lithium foil, copper-lithium composite tape, and magnesium-lithium alloy. By regulating the thickness and roughness of the lithium germanium phosphorus sulfur solid electrolyte, the interface contact between the electrode and the doped lithium germanium phosphorus sulfur solid electrolyte is improved, the interface resistance is effectively reduced, and the growth of lithium dendrites is inhibited, and the battery has good rate performance.

[0034] Example 1

[0035] A method for preparing a 5% molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte is implemented, comprising the following steps:

[0036] Step 1: Grind and mix Li2S, GeS2, MoO3 and P2S5 in a molar ratio of 4.95:0.95:0.05:1 under an argon atmosphere to obtain a mixed powder.

[0037] Step 2, sealing the mixed powder in a ball milling jar under an argon atmosphere; using a ball mill to mill the mixed powder; the speed of the ball mill is 300 to 500 rpm, and the ball milling time is 5 to 30 hours;

[0038] Step 3, pressing the ball-milled mixed powder into tablets, putting them into a sealed container, and packaging them after vacuuming;

[0039] Step 4, heating and calcining the sample packaged in a sealed container to 500-650° C., and performing a solid phase reaction for 5-48 hours;

[0040] Step 5: After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a composition of Li 9.9 Ge 0.95 Mo 0.05 P2S 12 Molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material.

[0041] Example 2

[0042] A method for preparing a 5% molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte is implemented, comprising the following steps:

[0043] Step 1, grinding and mixing Li2S, GeS2, MoO3, and P2S5 in a molar ratio of 4.95:0.95:0.05:1 under an argon atmosphere to obtain a mixed powder;

[0044] Step 2, sealing the mixed powder in a ball milling jar under an argon atmosphere; using a ball mill to mill the mixed powder; the speed of the ball mill is 500 rpm, and the ball milling time is 5 hours; the water content of the argon atmosphere is less than 1 ppm, and the oxygen content is less than 1 ppm;

[0045] Step 3, pressing the ball-milled mixed powder into a sheet, placing it into a sealed container, and packaging it after vacuuming; wherein the sheet thickness is 1 to 15 mm;

[0046] Step 4, heating and calcining the sample packaged in a sealed container to 500° C., and performing a solid phase reaction for 48 hours;

[0047] Step 5: After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a composition of Li 9.9 Ge 0.95 Mo 0.05 P2S 12 Molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material.

[0048] Example 3

[0049] A method for preparing a 10% molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte is implemented, comprising the following steps:

[0050] Step 1: Grind and mix Li2S, GeS2, Mo2S3 and P2S5 in a molar ratio of 4.9:0.9:0.05:1 under an argon atmosphere to obtain a mixed powder. The mixed powder is sealed in a ball mill;

[0051] Step 2, sealing the mixed powder in a ball milling jar; using a ball mill to ball mill the mixed powder; the speed of the ball mill is 300 to 500 rpm, and the ball milling time is 5 to 30 hours;

[0052] Step 3, pressing the ball-milled mixed powder into tablets, putting them into a sealed container, and packaging them after vacuuming;

[0053] Step 4, heating to 500-650° C., and performing solid phase reaction for 5-48 hours;

[0054] Step 5: After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a composition of Li 9.8 Ge 0.9 Mo 0.1 P2S 12 Molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material.

[0055] Example 4

[0056] A method for preparing a 10% molybdenum-doped lithium germanium phosphorus-sulfur solid electrolyte is implemented, comprising the following steps:

[0057] Step 1: Grind and mix Li2S, GeS2, Mo2S3 and P2S5 in a molar ratio of 4.9:0.9:0.05:1 under an argon atmosphere to obtain a mixed powder. The mixed powder is sealed in a ball mill;

[0058] Step 2, sealing the mixed powder in a ball milling jar under an argon atmosphere; using a ball mill to mill the mixed powder; the speed of the ball mill is 300 rpm, and the ball milling time is 30 hours; the water content of the argon atmosphere is less than 1 ppm, and the oxygen content is less than 1 ppm;

[0059] Step 3, pressing the ball-milled mixed powder into a sheet, placing it into a sealed container, and packaging it after vacuuming; wherein the sheet thickness is 1 to 15 mm;

[0060] Step 4, heating and calcining the sample packaged in a sealed container to 650° C., and performing a solid phase reaction for 5 hours;

[0061] Step 5: After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a composition of Li 9.8 Ge 0.9 Mo 0.1 P2S 12 Molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material. 9.8 Ge 0.9 Mo 0.1 P2S 12 The molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte was ball-milled to produce powders of different particle sizes.

[0062] Example 5

[0063] The invention relates to an application of a molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material in an all-solid-state secondary battery, specifically as follows: molybdenum-doped lithium germanium phosphorus sulfur is used as a solid electrolyte, and is assembled into an all-solid-state lithium secondary battery with a positive electrode and a lithium metal negative electrode. Preferably, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, nickel manganese binary, nickel cobalt manganese ternary, lithium iron phosphate, nickel cobalt aluminum oxide, and lithium-rich manganese-based positive electrode materials, preferably lithium cobalt oxide as the positive electrode active material. The lithium metal negative electrode includes at least one of pure lithium foil, copper-lithium composite tape, and magnesium-lithium alloy, preferably magnesium-aluminum alloy as the negative electrode active material.

[0064] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material, characterized in that The chemical general formula is: Li x Ge 1-y Mo y P2S 12 , where 9.5 < x < 10, 0 < y ≤ 0.1, and the molybdenum-doped lithium germanium phosphorus sulfur solid electrolyte material is prepared by the following preparation method: Step 1, according to the general formula: Li x Ge 1-y Mo y P2S 12 , weigh Li2S, GeS2, MoO3, and P2S5 in stoichiometric ratio under an inert atmosphere; Step 2, grinding and mixing Li2S, GeS2, MoO3 and P2S5 under an inert atmosphere, and ball milling using a ball mill under an inert atmosphere to obtain a mixed powder; Step 3, compressing the mixed powder under an inert atmosphere, placing it in a sealed container, and packaging it after evacuation; Step 4, heating and calcining the sample in the sealed container to perform a solid phase reaction; Step 5: After heating and calcining, naturally cool to room temperature to obtain a composition of Li x Ge 1-y Mo y P2S 12 Molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material.

2. The solid electrolyte material according to claim 1, characterized in that: The inert atmosphere in step 1-3 is argon gas, and the water content and oxygen content of the argon gas are less than 1 ppm and less than 1 ppm, respectively.

3. The solid electrolyte material according to claim 1, characterized in that: The rotation speed of the ball mill in step 2 is 300 to 500 rpm, and the ball milling time is 5 to 30 hours.

4. The solid electrolyte material according to claim 1, characterized in that: In step 3: the ball-milled mixed raw material is pressed into a sheet to prepare a sheet-shaped mixed raw material.

5. The solid electrolyte material according to claim 1, characterized in that: In step 4, the heating calcination temperature is 500-650° C., and the solid phase reaction time is 5-48 hours.

6. The solid electrolyte material according to claim 4, characterized in that: The thickness of the flaky mixed raw material is 1 to 15 mm.

7. The solid electrolyte material according to claim 1, characterized in that: The Li obtained in step 5 x Ge 1- y Mo y P2S 12 The molybdenum-doped lithium-germanium-phosphorus-sulfur solid electrolyte material is made into powder.

8. According to the solid electrolyte material of claim 7, the particle size of the powder is 10-1000 microns.

9. Use of the solid electrolyte material according to any one of claims 1 to 8 in an all-solid-state secondary battery.

Citation Information

Patent Citations

  • Lithium-containing argyrodite solid electrolyte with dopant and preparation method of lithium-containing argyrodite solid electrolyte

    CN111430808A

  • Sulfide solid electrolyte

    JP2019125502A